2020
DOI: 10.3126/jafu.v4i1.47065
|View full text |Cite
|
Sign up to set email alerts
|

Effect of plant growth regulators on flowering and fruit yield of cucumber (Cucumis sativus cv. Malini) in Chitwan, Nepal

Abstract: An experiment was done at Rambagh, Chitwan during March to May 2018 with the objective to evaluate the effect of plant growth regulators on growth, flowering and yield of cucumber (Cucumis sativus.) cv. Malini. The experiment consisted of nine treatments viz., control (no spray), silver nitrate 250 ppm spray, ethephon 250 ppm spray, gibberellic acid (GA3) 300 ppm spray, napthalene acetic acid (NAA) 50 ppm spray, silver nitrate 500 ppm spray, ethephon 250 ppm spray, gibberellic acid (GA3) 500 ppm spry, and napt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Increase in size of individual fruits with application of GA3 also reported by Vadigeri et al [5] in cucumber, Chowdary et al [6] in cucumber where GA3 200 ppm significantly increased fruit weight and Nagamani et al [7] who reported that application of GA3 significantly enhanced fruit weight in bitter gourd. Sapkota et al [8] also observed similar findings in cucumber. Finally, the highest fruit length was recorded in treatment with GA3 at 150 ppm.…”
Section: Yield Parametersmentioning
confidence: 53%
“…Increase in size of individual fruits with application of GA3 also reported by Vadigeri et al [5] in cucumber, Chowdary et al [6] in cucumber where GA3 200 ppm significantly increased fruit weight and Nagamani et al [7] who reported that application of GA3 significantly enhanced fruit weight in bitter gourd. Sapkota et al [8] also observed similar findings in cucumber. Finally, the highest fruit length was recorded in treatment with GA3 at 150 ppm.…”
Section: Yield Parametersmentioning
confidence: 53%
“…Hossain et al (2006) also found that the application of GA 3 at different level (<70 ppm) at pre-flowering stage significantly influenced flowering behavior and fruiting characteristics in bitter gourd. Sapkota et al(2020) reported that NAA 50 ppm had higher number of male and female flower over NAA 100 ppm in cucumber. PGRs treatments had significantly lowered the male to female flower ratio (Table -2).…”
Section: Phenological Characteristics and Sex Expressionmentioning
confidence: 98%
“…Ghani et al (2013) stated that the PGRs have great potentialities to influence plant growth morphogenesis. Sapkota et al(2020) reported that NAA@50 ppm has better fruit yield (70.17 t/ha) than NAA @ 100 ppm (54.39 t/ha) in cuumber cultivar Malini in Chitwan condition. Dalai et al(2015) found that number of female flower per plant in cucumber treated with GA @ 30 ppm(24.21) and NAA @ 50 ppm(25.21) was more in comparision to control(19.31).…”
Section: Introductionmentioning
confidence: 97%
“…Cucumber plants bear a variety of floral forms and morphology, including hermaphrodite flowers, staminate, and pistillate, which occur in different arrangements and produce several types of sexual expression [10,20].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous former studies have shown that exogenous application of plant growth regulators can cause a change in the sex ratio and sequence if it is applied in the stage of the second leaf until the fourth leaf, which is the critical or effective stage in which either sex can be suppressed or enhanced [10,20]. Other studies have also reported that exogenous application of PGRs may shift sexual expression in cucurbits toward femaleness, increasing the number of pistillate flowers, the number of fruit/plant, and the weight of individual fruit, as well as yield [21].…”
Section: Introductionmentioning
confidence: 99%